The expressions of matrix metalloproteinase-9, estrogen receptor, and progesterone receptor in thin endometrial tissue and their significance. (3rd June 2022) - Li, Lin-Hong; Shi, Gang; Pan, Jin-Bing; Wang, Cai-Hong; Zhao, Min; Zhang, Xiu-Ping
Abstract: Objective: This study aims to investigate the expressions of matrix metalloproteinase-9 (MMP-9), estrogen receptor (ER), and progesterone receptor (PR) in thin endometrium. Methods: Patients who received treatment in our hospital between January 2018 and September 2020 were enrolled. Endometrial thickness was measured using transvaginal ultrasound; in patients with a midluteal phase endometrial thickness of <7 mm, a sample of endometrial tissue was obtained using a hysteroscope, and the MMP-9, ER, and PR expressions were detected using immunohistochemistry. In addition, the number of endometrial glands was calculated in a complete field of view under a low-power (100×) microscope, and the serum estrogen and progesterone levels were determined. Following hormone therapy, the midluteal phase endometrial thickness was measured again using transvaginal ultrasound, and the patients were divided into two groups: the thin endometrium group and the normal endometrium group ( n  = 50, each). Patients in the thin endometrium group had an endometrial thickness of <7 mm, while patients in the normal endometrium group had an endometrial thickness of 7–10 mm. Results: The number of endometrial glands as well as the ER and MMP-9 expressions were lower in the thin endometrium group than in the normal endometrium group; the differences were statistically significant ( p  < .05). The receiver operator characteristic curve revealed that ER and MMP-9 had a high prediction accuracy in patients with refractory thin endometrium, while the number of endometrial glands was moderately predictive. Conclusion: Compared with other patients with thin endometrium, patients with refractory thin endometrium had a reduced the number of endometrial glands and significantly lower ER and MMP-9 expressions.